Avaliação do efeito da ponta do apalpador na medição da rugosidade em superfícies fresadas, mandriladas e brunidas - Souza, Cláudio Costa (2019)
This work deals with evaluation of the effect of the stylus tip radius on the roughness parameters on milled, bored and honed surfaces of crankcase of hermetic compressors manufactured in gray cast iron. Roughness measurements were carried out on machined surfaces of 10 crankcases of hermetic compressors using a 2 and a 5 µm stylus tip radius. For milled and bored surfaces Rp, Rv, Rz, Rt, Ra, Rq and RΔq roughness parameters were obtained, whereas for honed surfaces Rk, Rpk and Rvk were studied. From the obtained results it was concluded that for milled and bored surfaces, only the values of RΔq presented statistically significant differences, considering a confidence level of 95 %. However, particular attention should be given to the Rv parameter whose p-values were higher than 0.05, but very close to it. For honed surfaces, the average values of Rk and Rpk parameters were higher for measurements carried out using a 5 µm stylus tip radius, due to the increase of the peak radius of curvature. No statistically significant difference related to Rpk, Rk and Rvk parameters was identified.